GauseR: Simple methods for fitting Lotka‐Volterra models describing Gause's "Struggle for Existence". Issue 23 (26th October 2020) - Mühlbauer, Lina K.; Schulze, Maximilienne; Harpole, W. Stanley; Clark, Adam T.
Abstract: Point 1: The ecological models of Alfred J. Lotka and Vito Volterra have had an enormous impact on ecology over the past century. Some of the earliest—and clearest—experimental tests of these models were famously conducted by Georgy Gause in the 1930s. Although well known, the data from these experiments are not widely available and are often difficult to analyze using standard statistical and computational tools. Point 2: Here, we introduce the gauseR package, a collection of tools for fitting Lotka‐Volterra models to time series data of one or more species. The package includes several methods for parameter estimation and optimization, and includes 42 datasets from Gause's species interaction experiments and related work. Additionally, we include with this paper a short blog post discussing the historical importance of these data and models, and an R vignette with a walk‐through introducing the package methods. The package is available for download at github.com/adamtclark/gauseR. Point 3: To demonstrate the package, we apply it to several classic experimental studies from Gause, as well as two other well‐known datasets on multi‐trophic dynamics on Isle Royale, and in spatially structured mite populations. In almost all cases, models fit observations closely and fitted parameter values make ecological sense. Point 4: Taken together, we hope that the methods, data, and analyses that we present here provide a simple and user‐friendly way to interact with complex ecological data. We are optimistic that these methods will be especially useful to students and educators who are studying ecological dynamics, as well as researchers who would like a fast tool for basic analyses. Abstract : The competition and predation experiments conducted by G. F. Gause in the first half of the 20th century remain some of the best‐known empirical tests of Alfred Lotka and Vito Volterra's models of species interactions. Here, we collate data from more than 40 of these experiments, along with basic tools for fitting the Lokta‐Volterra models to empirical data.